Copovidone-Based Stable Nebivolol Hydrochloride Formulation: Dissolution and Characterization Studies: Stable Nebivolol Hydrochloride Formulation - Swamiappan, Sasikumar; Shaikh, Tauseef (Iranian Journal of Pharmaceutical Sciences, 2023)
Copovidone Based Stable Nebivolol Hydrochloride Formulation: Dissolution and Characterization Studies. The study aimed to develop a formulation for the poorly water-soluble drug Nebivolol Hydrochloride. The formulation was carried out in two stages. Stage I attempts to enhance the drug’s solubility, while stage II deals with the development of a drug-incorporated tablet formulation. Various strategies with different solid dispersion techniques, like solvent evaporation, melt fusion, and kneading, were used to improve the drug’s solubility. Drugs and carriers were mixed with the ratios 1:1, 1:2, 1:3, and 1:4. Apart from the solid dispersion method, the hydrophilic carrier was activated with an acidifier and then mixed with the drug. Preformulation studies were conducted, which included API characterization, solubility measurement over a physiological pH range, and drug-excipients compatibility study. FTIR, DSC, and XRD characterized the developed solid dispersion, which shows the drug exists in the amorphous form in the solid dispersion with no molecular interaction. The dissolution profile revealed a significant improvement in drug solubility with solid dispersion compared to pure drugs. Solid dispersion prepared with Drug, Plasdone, and Tartaric Acid exhibits the most improved solubility and formulated immediate release tablet. Stability studies indicate excellent stability of formulation over six months at accelerated and real-time conditions.